Exploring Coulomb stress changes on active structures in Taiwan inferred from decadal GNSS observations - Lin, Li-Chieh J.; Chuang, Ray Y.; Nishimura, Takuya (Earth, planets, and space, 2025)
Although earthquakes cannot yet be accurately predicted, many scientific endeavors have been put forth to forecast the probabilities of earthquake occurrences, aiming to mitigate seismic hazards. Throughout the course of equipment and processing improvements in the last decades, GNSS data has shown great abilities for seismic hazard assessments. As one of the most active plate boundaries, the island of Taiwan is subject to high seismic potential, but the link between geodetic observations and seismic hazards is less addressed. In this study, we explored the stress evolution of active structures in Taiwan induced by 1) interseismic loading and 2) coseismic stress transfer from nearby major earthquakes. For coseismic stress transfers, we utilized the Coulomb software with published coseismic slip distributions. Interseismically, we used a densely installed GNSS network to infer the long term stress build-ups. We separated GNSS time series between each major earthquake in the region and calculated interseismic velocities between events to infer the Coulomb stress changes of the studied faults across different periods. Results showed that the interseismic stress loading of some faults neighboring major earthquakes had changed. Faults in central Taiwan showed rapid stress loading from 2003 to 2007, which could result from the post-earthquake effect of the 1999 Chi-Chi earthquake. The southern segment of the Longitudinal Valley fault experienced a negative stress change after the 2013 Ruisui earthquake, which might lead to possible triggered creep along the fault that is often considered stress release. However, the faults in southern Taiwan did not have significant stress changes after the 2016 Meinong earthquake. The effect of the earthquake event might be insignificant in terms of altering the surrounding stress field. Graphical Abstract